Evaluation of Serum Human Kidney Injury Molecule-1 and N-Acetyl-β-D-Glucosaminidase as Early Markers of Kidney Injury in Patients with β-Thalassemia Major in Diyala Governorate - Hassan, Hiba Abid Al-Hussein; Jassim, Hind Salman (Iraqi Journal of Science, 2024)
Thalassemia is a genetic disease identified by a defect in the production of one or more globin chains. This study was aimed at determining the possibility of using "serum kidney injury molecule-1 (KIM-1)" and "N-acetyl-β-D-glucosaminidase (NAG)" in the diagnosis of early renal damage in thalassemia patients. Serum biomarkers (CBC, urea, creatinine, KIM-1, and NAG) were determined in 45 patients with major thalassemia with an age range of 4-45 years who attended Baquba General Hospital. A significant increase in S.KIM-1 and S.NAG levels in patients compared with controls. The level of KIM was positively correlated with that of urea and creatinine in comparison with control. Also, the level of NAG was strongly positively correlated with the level of KIM-1 (p = 0.000) and had a moderately positive correlation with urea and creatinine (p = 0.000). According to ROC, KIM-1 had a sensitivity of 95.56% and a specificity of 88.89%, while NAG had a sensitivity of 100% and a specificity of 75.6%. This study concluded that S.KIM-1 and S.NAG are highly promising biomarkers for the detection of "acute kidney injury" in an early stage before elevated urea and creatinine in thalassemia patients.